Análise do atendimento em centro de atenção psicossocial do tipo II, na perspectiva do público infantojuvenil - Melo, Olindina Ferreira (2022)
The main objective of this study was to analyze the care provided at the Psychosocial Care Center, from the perspective of child care, in Sobral, Ceará, Brazil. The methodological assumptions defined focused on three moments, the first and second moments of epidemiological, observational and descriptive character about the population served, infrastructure and pharmacy services. The third moment was about the characteristics of health professionals who work in this center from 2016 to 2019. The following variables were analyzed: age, place of residence, referral received and diagnosis hypothesis, structural aspects such as meeting room, cafeteria, storeroom, bathroom with clothing for employees, Storage of Cleaning Material, utility room, outdoor living area , external area for boarding and shelter for gas cylinders). The municipality has 39 Family Health Centers, 18 of which are located in rural areas, 01 CAPS-General and 01 CAPS-AD. The results obtained were identified 1,942 attendances in the referred period. It was found that, in 2018, there was a greater number of services for the general public (adults and elderly) (30.6%) and children (35.6%). In 2019, there was a higher record of assistance to adolescents, with 33.5%. In the distribution by year, it was found that in 2016, there were more visits to children (21.22%) and adolescents (20.84%), both in September. Regarding the geopolitical territory of residence of users, most of the population, children and adolescents lived in the urban area. The age group of children residing in the urban area was 1-6 years old and adolescents between 13-15 years old. As for the status of the children's medical records, it was observed that 55.72% were active and the adolescents' medical records, 51.28% were inactive. When identifying the outcome of the care, it was noticed that both children (50.70%) and adolescents (50.98%) were referred to the family health center. In identifying the diagnostic hypothesis, there was a record of hyperkinetic disorders for children and depression for adolescents. As for the physical spaces of the center, it was observed that they did not have a play space for children, toilets for people with special needs, meeting room, cafeteria, storeroom, bathroom with clothing for employees, deposit of cleaning material, utility room, outdoor living area, for boarding and shelter for gas cylinders. The pharmacy's infrastructure was classified as precarious, although the availability of essential medicines to children and adolescents is excellent and the conditions of conservation and storage of the pharmacy's medicines are satisfactory.